AMP-activated protein kinase controls exercise training- and AICAR-induced increases in SIRT3 and MnSOD - Brandauer, Josef; Andersen, Marianne A.; Kellezi, Holti; Risis, Steve; Frøsig, Christian; Vienberg, Sara G.; Treebak, Jonas T. (Frontiers in Physiology, 2015)
The mitochondrial protein deacetylase sirtuin (SIRT) 3 may mediate exercise training-induced increases in mitochondrial biogenesis and improvements in reactive oxygen species (ROS) handling. We determined the requirement of AMP-activated protein kinase (AMPK) for exercise training-induced increases in skeletal muscle abundance of SIRT3 and other mitochondrial proteins. Exercise training for 6.5 weeks increased SIRT3 (p<0.01) and superoxide dismutase 2 (MnSOD; p<0.05) protein abundance in quadriceps muscle of wild-type (WT; n=13-15), but not AMPK α2 kinase dead (KD; n=12-13) mice. We also observed a strong trend for increased MnSOD abundance in exercise-trained skeletal muscle of healthy humans (p=0.051; n=6). To further elucidate a role for AMPK in mediating these effects, we treated WT (n=7-8) and AMPK α2 KD (n=7-9) mice with 5-amino-1-β-D-ribofuranosyl-imidazole-4-carboxamide (AICAR). Four weeks of daily AICAR injections (500 mg/kg) resulted in AMPK-dependent increases in SIRT3 (p<0.05) and MnSOD (p<0.01) in WT, but not AMPK α2 KD mice. We also tested the effect of repeated AICAR treatment on mitochondrial protein levels in mice lacking the transcriptional coactivator peroxisome proliferator-activated receptor γ-coactivator 1α (PGC-1α KO; n=9-10). Skeletal muscle SIRT3 and MnSOD protein abundance was reduced in sedentary PGC-1α KO mice (p<0.01) and AICAR-induced increases in SIRT3 and MnSOD protein abundance was only observed in WT mice (p<0.05). Finally, the acetylation status of SIRT3 target lysine residues on MnSOD (K122) or oligomycin-sensitivity conferring protein (OSCP; K139) was not altered in either mouse or human skeletal muscle in response to acute exercise. We propose an important role for AMPK in regulating mitochondrial function and ROS handling in skeletal muscle in response to exercise training.